ANALYSIS OF WORK ENVIRONMENT FACTOR AND WORKLOAD ON THE FATIGUE LEVEL OF OIL DRILLING WORKER IN JATIBARANG FIELD DRILLING AREA (CASE STUDY: OIL DRILLING WORK PT.X ON DAY-SHIFT) - Akbar, Ari
Work exhaustion can be influenced by work environment factors and workload. PT X is one of the companies that conduct business activities in the upstream sector of the oil and gas sector including Exploration and Exploitation. All drilling activities in the Jatibarang drilling area have a high risk of fatigue for workers due to exposure: heavy equipment use, noise, direct exposure to solar heat, and working time. Work fatigue measurements were carried out before and after work using a reaction timer and subjective self rating test questionnaire. The evaluation results show that the type of floorman work is included in the category of heavy workload with an average workload of 626.06 ± 7.81 kcal / hour. The roustabout, mudboy, and service crew group activities are included in the medium workload category with an average workload of 328.83 ± 2.64 kcal / hour, 335.94 ± 7.88 kcal / hour, and 279.93 ± 2.00 kcal / hour. The results of evaluation of temperature values at the beginning of the shift and middle shift in the floorman work activity group, roustabout and mudboy exceed the threshold value (NAB). work fatigue in floorman, roustabout, and mudboy work is included in the category of mild fatigue with each increase in reaction time by 303.5 ± 64,015 milliseconds, 235.5 ± 27,766 milliseconds, and 247.25 ± 6,020 milliseconds. Based on the spearman correlation test on the type of floorman work there is a correlation between age and reaction time with p-value of 0.002 (p <0.05) and work experience with the reaction time with p-value of 0.005 (p <0.05). Meanwhile, related to the spearman relationship between oil drilling workload and reaction time with a p-value of 0.004. Based on the results of linear regression, heat is a more important factor than the work comparison seen from the same coefficient